Gods and robots : myths, machines, and ancient dreams of technology - Mayor, Adrienne, 1946- (Princeton University Press, 2018)
"The fascinating untold story of how the ancients imagined robots and other forms of artificial life--and even invented real automated machines The first robot to walk the earth was a bronze giant called Talos. This wondrous machine was created not by MIT Robotics Lab, but by Hephaestus, the Greek god of invention. More than 2,500 years ago, long before medieval automata, and centuries before technology made self-moving devices possible, Greek mythology was exploring ideas about creating artificial life--and grappling with still-unresolved ethical concerns about biotechne, "life through craft." In this compelling, richly illustrated book, Adrienne Mayor tells the fascinating story of how ancient Greek, Roman, Indian, and Chinese myths envisioned artificial life, automata, self-moving devices, and human enhancements--and how these visions relate to and reflect the ancient invention of real animated machines."--Provided by publisher